2008
DOI: 10.1111/j.1349-7006.2008.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse large B‐cell lymphoma after transformation from low‐grade follicular lymphoma: morphological, immunohistochemical, and FISH analyses

Abstract: (1) FL occurs over a broad range of ages, and most cases are manifested initially in lymph nodes.The risk of FL transformation has been reported as being approximately 20% at 8 years.(2,3) Transformation to DLBCL is observed frequently, with cells most commonly resembling centroblasts, (4) but occasionally resembling anaplastic large cells with CD30 expression.(5) Rare cases have transformed to Burkitt or Burkitt-like lymphoma, (6) or precursor B-lymphoblastic lymphoma/acute lymphoid leukemia.(7) Moreover, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
41
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…(14,15) However, few histopathological and immunohistochemical analyses of transformed FL have been performed. (12,16,17) Hans et al (16) reported that FL grade 3 cases with a predominant diffuse component (>50% diffuse) had a significantly worse overall survival and event-free survival than the remaining FL grade 3 cases.Since 2000, DLBCL has been subdivided into germinal center B-cell (GCB) and non-GCB subgroups (including the activated B-cell phenotype [ABC] and type 3 phenotype) by using the cDNA microarray technique. (18,19) The GCB subgroup shows a better outcome and includes cases with a translocation (14;18)(q32;q21).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…(14,15) However, few histopathological and immunohistochemical analyses of transformed FL have been performed. (12,16,17) Hans et al (16) reported that FL grade 3 cases with a predominant diffuse component (>50% diffuse) had a significantly worse overall survival and event-free survival than the remaining FL grade 3 cases.Since 2000, DLBCL has been subdivided into germinal center B-cell (GCB) and non-GCB subgroups (including the activated B-cell phenotype [ABC] and type 3 phenotype) by using the cDNA microarray technique. (18,19) The GCB subgroup shows a better outcome and includes cases with a translocation (14;18)(q32;q21).…”
mentioning
confidence: 99%
“…(23) The outcome of the patients with DLBCL transformed from FL with t(14;18) is unclear, although we recently reported that this fusion does not affect clinical outcome. (17) The aim of this study is to clarify the histopathological prognostic parameters of DLBCL transformed from FL. Eleven histopathological parameters influencing progression-free survival (PFS) and ⁄ or OS were evaluated using univariate and multivariate analyses, including the presence of synchronous ⁄ asynchronous FL and DLBCL, the proportion of DLBCL, the highest grade of FL, expressions of CD10, Bcl-2, Bcl-6, MUM1, cMyc, and Ki-67, classification as GCB ⁄ non-GCB subgroups, and detection of IGH/BCL2 fusion using fluorescence in situ hybridization (FISH) analysis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…(10,11) This transformation is usually associated with acceleration of the clinical course. (12) Transformed FLs generally retain the t(14;18) translocation, (13) and it is believed that other genetic abnormalities are necessary in order for this transformation to occur. These secondary genetic events associated with histological transformation include c-myc amplification and translocation, (14,15) bcl-6 translocation, (16) TP53 mutation, (17) P16 gene inactivation, (18) and c-REL amplification.…”
mentioning
confidence: 99%